(untitled) (Fourth World Journal, 2025)
This article is a condensed version of a case study of Gram Sahas in Scheduled Areas of Rajasthan, India conducted under a University Grants Commission of India sponsorship considering the Panchayats (Extension to Scheduled Areas) Act, 1996 (PESA). The study arose from the scholarly intent of the researcher to probe into the apparatus created in the wake of the 73rd constitutional amendment with regard to specific provisions for Scheduled Areas in general and Rajasthan in particular.